Maturidade e potencial fisiológico de sementes e qualidade de mudas de Anadenanthera colubrina (Vell.) Brenan em função do local de colheita - Cruz, Maria Soraia Fortado Vera (2019)
Anadenanthera colubrina (Vell.) Brenan has several purposes such as timber, medicinal, landscape and beekeeping and for the recovery of degraded areas. In view of the above, this work had as general objective to characterize the maturation and the physiological potential of A. colubrina seeds and seedlings from Western Paranaense, Brazil. First, in the evaluation of the physiological maturity of the seeds, the fruits collected from matrices located in Marechal Cândido Rondon were mixed and then classified into four maturation stages according to fruit color (moderate yellow, dark brown, dark brown reddish and light brown). The seeds were evaluated for biometric characteristics and tested for germination and vigor. The experiments were conducted in a completely randomized experimental design with four treatments and five replicates of 20 seeds. The averages were compared by the Tukey test at 5% of error probability. To evaluate the quality of seeds and seedlings associated to different collection sites, mature fruits were collected in three municipalities of the West of Paraná (Marechal Cândido Rondon, Santa Helena and Diamante D'Oeste). The seeds from each municipality were mixed and homogenized, constituting a lot. The seed quality was characterized by the following attributes: mass of one thousand seeds, germination test, mean germination time, germination speed index, dry matter mass of seedlings and seed respiration test. The seedlings of A. colubrina were conducted with or without irrigation. At the end of the experiments, the following quality attributes were measured: plant height, collection diameter, shoot dry mass, root and total mass, Dickson quality index and root electrolyte loss. The trials were conducted in a completely randomized design. To evaluate the influence of provenance on seed and seed vigor, principal component analyzes were performed. And to verify the relationships between seed quality under the production of good quality seedlings, track analysis was performed. The seeds of the fruits with dark brown and reddish-brown color showed drastic reduction in water content and high germinative potential and vigor. Therefore, the color of the fruit was shown to be a good indicator of the physiological maturity of the A. colubrina seeds, and the fruits with dark reddish-brown and light brown indicated the ideal time of the seed harvest. The sites of origin were separated into two quality groups of seeds and seedlings, in which Diamante D'Oeste and Santa Helena distinguished themselves as being of greater vigor, in relation to that of Marechal Cândido Rondon. In addition, it was verified that the physiological potential of the seeds, under the conditions evaluated in this study, interferes in the initial development of the seedlings, being the average germination time, the germination speed index and the total dry mass of the seedlings, the recommended attributes to select seeds with high physiological potential, which will reflect on quality seedlings in nurseries.